2013
DOI: 10.1074/jbc.m113.502948
|View full text |Cite
|
Sign up to set email alerts
|

Glycolytic ATP Fuels the Plasma Membrane Calcium Pump Critical for Pancreatic Cancer Cell Survival

Abstract: Background: Pancreatic cancer cells exhibit up-regulated glycolysis.Results: Inhibition of glycolysis, but not mitochondrial metabolism, induced ATP depletion, plasma membrane calcium pump (PMCA) inhibition, Ca2+ overload, and cell death.Conclusion: Glycolytic ATP fuels the PMCA in pancreatic cancer.Significance: Glycolytic regulation of the PMCA may represent a novel chemotherapeutic target for pancreatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
57
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(65 citation statements)
references
References 53 publications
6
57
1
1
Order By: Relevance
“…Since MIA PaCa-2 cells almost exclusively expressed PMCA4 at both the protein and mRNA level, this suggests that MIA PaCa-2 represents a good cellular model of PMCA4-overexpressing PDAC that can be taken forward for further functional studies. Moreover, as our previous studies by James, A.D. et al [9,10] suggested that MIA PaCa-2 cells are more reliant on glycolytically-derived ATP than the related PANC-1 cells, this makes MIA PaCa-2 an ideal cellular model to examine the role of PMCA4 on PDAC cancer hallmarks, particularly the metabolic shift towards glycolysis.…”
Section: Pmca4 Is the Major Pmca Isoform Expressed In Mia Paca-2 Pancmentioning
confidence: 96%
See 2 more Smart Citations
“…Since MIA PaCa-2 cells almost exclusively expressed PMCA4 at both the protein and mRNA level, this suggests that MIA PaCa-2 represents a good cellular model of PMCA4-overexpressing PDAC that can be taken forward for further functional studies. Moreover, as our previous studies by James, A.D. et al [9,10] suggested that MIA PaCa-2 cells are more reliant on glycolytically-derived ATP than the related PANC-1 cells, this makes MIA PaCa-2 an ideal cellular model to examine the role of PMCA4 on PDAC cancer hallmarks, particularly the metabolic shift towards glycolysis.…”
Section: Pmca4 Is the Major Pmca Isoform Expressed In Mia Paca-2 Pancmentioning
confidence: 96%
“…As PMCA4 is the major PMCA isoform expressed in MIA-PaCa-2, we predicted that PMCA4 is functionally critical for Ca 2+ efflux. After establishing conditions which yielded ≥70% of PMCA4 expression knockdown, we then wanted to confirm that this led to decreased PMCA activity using our in situ Ca 2+ clearance assay [9,10].…”
Section: Pmca4 Is the Major Functional Ca 2+ Efflux Pathway In Mia Pamentioning
confidence: 99%
See 1 more Smart Citation
“…77 Bunun nedeni, Otto Warburg'un 100 yıl önce tanımladığı kanser hücrelerinin enerji metabolizmalarını glikolize çevirmeleriyle, hücresel enerji metabolizmasının yeniden programlanması olabilir. [78][79][80] Glikolizin düzenlenmesinde kalsiyum sinyalinin muhtemel rolü üzerine yapılan çalışma-larda, glikolize dönüşüm ve kanser hücrelerinin kalsiyum pompa yakıtı olarak glikoz-üretimli ATP kullanımı gerektiği görülmüştür. 78 Kalsiyum sinyalinin oldukça kritik olduğu savunulan fakat tam olarak henüz aydınlatılmayan diğer bir kanser biyoloji konusu tümör mikro çevredir.…”
Section: Kalsi̇yum Si̇nyali̇ Ve Kanserunclassified
“…In addition, evidence that the PMCAs may be a potential therapeutic target for chemotherapy-resistant cancers has been found in two further cell types. First, PMCA1 expression is increased in cisplatinresistant human ovarian adenocarcinoma cells compared with cisplatin-sensitive cells (348), and second, the resistance to cell death conferred upon pancreatic cancer cells by a switch in metabolism from mitochondrial to glycolytic pathways can be reversed by inhibiting glycolysis, an effect which leads to PMCA inhibition, Ca 2ϩ overload, and cell death (167). Hence, although the field is still in its infancy, the identified roles for different PMCA isoforms in regulating tumorigenesis, progression, and survival in various tissues may lend themselves towards targeting for the treatment of cancers in specific cell types.…”
Section: Pmca and Other Cancersmentioning
confidence: 99%